Method for manufacturing electrode and method for manufacturing battery

By controlling the moisture content during the electrode manufacturing process and using conductive rollers to correct the structure, the damage caused by electrode hardening is solved, and the success rate of electrode manufacturing and battery performance is improved.

JP2025018737AActive Publication Date: 2025-02-06KK TOSHIBA
View PDF 8 Cites 0 Cited by

Patent Information

Application Number
JP2023122714
Authority / Receiving Office
JP · JP
Patent Type
Applications
Current Assignee / Owner
Filing Date
2023-07-27
Publication Date
2025-02-06
Estimated Expiration
2043-07-27

AI Technical Summary

Technical Problem

Existing electrodes are prone to hardening during the manufacturing process, resulting in damage and peeling, affecting battery performance.

Method used

By controlling the moisture content between 1000% and 10000% during the electrode manufacturing process, the structure is corrected using conductive rollers to avoid stress differences during drying, combined with appropriate pressure and tension treatment, the electrodes are prevented from breaking during pressing and cutting.

Benefits of technology

Effectively prevent electrodes from breaking during pressing and cutting, improving the success rate of electrode manufacturing and battery performance.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure 2025018737000001_ABST
    Figure 2025018737000001_ABST
Patent Text Reader

Abstract

To provide a method for manufacturing an electrode and a method for manufacturing a battery which can reduce generations of failures in the manufacturing.SOLUTION: According to an embodiment, there is provided a method for manufacturing an electrode including the steps of: applying a slurry including at least one of a niobium-containing oxide and a titanium-containing oxide and water to a collector and obtaining a structure (Step 1); drying the slurry and forming an active material containing layer which contains water by the Karl-Fischer method in the range from 1000 mass ppm to 10000 mass ppm, both inclusive (S2); and pressing the structure (S3).SELECTED DRAWING: Figure 1
Need to check novelty before this filing date? Find Prior Art

Description

[Technical field]

[0001] The embodiments relate to a method for manufacturing an electrode and a method for manufacturing a battery. [Background technology]

[0002] In order to improve the life performance of electrodes using niobium titanium-containing oxide, hydrophilic binders such as carboxymethyl cellulose (CMC) have been added to the electrodes. However, this electrode has a problem in that the active material-containing layer tends to harden, causing defects such as breakage and chipping during pressing and cutting. [Prior art documents] [Patent documents]

[0003] [Patent Document 1] JP 2019-53944 A Summary of the Invention [Problem to be solved by the invention]

[0004] An object of the embodiments is to provide a method for manufacturing an electrode and a method for manufacturing a battery that can reduce the occurrence of defects during manufacturing. [Means for solving the problem]

[0005] According to an embodiment, the present invention includes a step of obtaining a structure by applying a slurry containing at least one of a niobium-containing oxide and a titanium-containing oxide and water to a current collector; a step of drying the slurry to form an active material-containing layer having a moisture content of 1000 ppm by mass or more and 10000 ppm by mass or less according to the Karl Fischer method; and pressing the structure.

[0006] According to the embodiment, a method for producing an electrode group includes the steps of: using the electrode obtained by the method according to the embodiment as a first electrode; and disposing a separator between the first electrode and a second electrode to produce an electrode group; A step of housing the electrode group in an exterior member; and causing the electrode group housed in the exterior member to retain a non-aqueous electrolyte. [Brief description of the drawings]

[0007] [Figure 1] FIG. 4 is a flow diagram illustrating an example of a method according to an embodiment. [Diagram 2] FIG. 2 is a schematic diagram showing an example of coating and drying in the method of the embodiment. [Diagram 3] FIG. [Figure 4] 4 is a cross-sectional view taken along line IV-IV of the structure shown in FIG. 3. [Diagram 5] 4 is a cross-sectional view taken along line VV of the structure shown in FIG. 3. [Figure 6] FIG. 4 is a side view showing a state in which a portion of the structure without an active material-containing layer is sandwiched between a pair of rollers. [Figure 7] FIG. 2 is a cross-sectional view taken along a direction perpendicular to the conveying direction, showing a state in which a portion of the structure without an active material-containing layer is sandwiched between a pair of rollers. [Figure 8] FIG. 1 is a schematic perspective view showing an example of a structure wound in a roll shape. [Figure 9] FIG. 4 is a schematic perspective view showing an example of pressing and winding in the method of the embodiment. [Figure 10] FIG. 10 is an enlarged cross-sectional view showing the pressing process shown in FIG. [Figure 11] FIG. 4 is a schematic plan view showing an example of cutting in the method of the embodiment. [Figure 12] FIG. 2 is a plan view showing an electrode manufactured by the method of the embodiment. [Figure 13] FIG. 13 is a plan view showing an electrode having a wrinkled tab. [Figure 14] FIG. 2 is a partially cutaway perspective view of a battery manufactured by the method of the embodiment. [Figure 15] FIG. 15 is an enlarged cross-sectional view of a portion indicated by B in FIG. [Figure 16] FIG. 4 is a perspective view showing another example of a laminated electrode group manufactured by the method of the embodiment. [Figure 17] 4 is a cross-sectional view of a battery manufactured by a method according to an embodiment, taken in a direction perpendicular to the terminal extending direction. FIG. [Figure 18] FIG. 18 is an enlarged cross-sectional view of a portion indicated by A in FIG. [Figure 19] FIG. 6 is a flow diagram illustrating another example of a method according to an embodiment. [Figure 20] FIG. 4 is a plan view showing a housing used in the second drying step of the method according to the embodiment. [Figure 21] 21 is a cross-sectional view of the housing of FIG. 20 taken along line XXI-XXI. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS

[0008] (First embodiment) The first embodiment relates to a method for manufacturing an electrode.

[0009] An electrode produced by applying a slurry containing at least one of a niobium-containing oxide and a titanium-containing oxide and water to a current collector, drying, pressing, and cutting is hard. Therefore, it is easy to automate the process of producing a stacked electrode group by disposing a separator between this electrode and a counter electrode. On the other hand, breakage or chipping is likely to occur during pressing or cutting.

[0010] The method of the embodiment includes a step of obtaining a structure by applying a slurry containing at least one of a niobium-containing oxide and a titanium-containing oxide and water to a current collector; a step of drying the slurry to form an active material-containing layer having a moisture content of 1000 ppm by mass or more and 10000 ppm by mass or less, as measured by the Karl Fischer method; and pressing the structure.

[0011] According to the method of the embodiment, at least when pressing and cutting are performed, it is possible to suppress the occurrence of breakage and chipping in the structure due to pressing and cutting.

[0012] The method of the embodiment will be described below with reference to FIGS.

[0013] The method for producing an electrode according to the embodiment may include steps S1 to S4 shown in FIG.

[0014] First, the slurry coating S1 and the first drying S2 will be described.

[0015] 2 shows an example of an apparatus used in the slurry coating S1 and the first drying S2. This apparatus includes a slurry coating apparatus 20, a drying furnace 21, and a curvature correction section 22. The slurry coating apparatus 20 includes a slurry storage section 23, a first die coater 24, and a second die coater 25. A current collector roll 26 on which a current collector 3a (e.g., a negative electrode current collector 3a) to be treated is wound in a roll shape is disposed on the upstream side of the transport path F1. A winding roller 27 is disposed on the downstream side of the transport path F1. The current collector 3a sent out from the current collector roll 26 moves along the transport path F1 and is wound up by the winding roller 27.

[0016] The first die coater 24 is located above the current collector 3a moving along the transport path F1. The second die coater 25 is located below the current collector 3a moving along the transport path F1. The second die coater 25 is located downstream of the first die coater 24. The slurry storage unit 23 supplies the slurry to the first die coater 24 via a slurry supply flow path 23a. The slurry storage unit 23 also supplies the slurry to the second die coater 25 via another slurry supply flow path (not shown). The slurry storage unit 23 includes, for example, a slurry storage container and a liquid feed pump (not shown).

[0017] The drying furnace 21 is disposed downstream of the conveying path F1 from the slurry coater 20. The drying furnace 21 has an inlet (not shown) through which the current collector 3a (hereinafter referred to as the structure) coated with the slurry is inserted into the drying furnace 21, and an outlet (not shown) through which the structure that has moved within the drying furnace 21 along the conveying path F1 is discharged.

[0018] The curvature correction unit 22 is disposed downstream of the first die coater 24 and the second die coater 25, at any one or more locations in the drying furnace 21, and between the drying furnace 21 and the take-up roller 27. By disposing the curvature correction unit 22 downstream of the first die coater 24 and the second die coater 25, the curvature correction unit 22 does not affect the surface coated by the first die coater 24 and the second die coater 25, and the flatness of the coated surface can be maintained. As shown in Figs. 6 and 7, the curvature correction unit 22 can be composed of a pair of rollers. The curvature correction unit 22 is composed of a guide roller 28 located above the structure moving along the conveying path F1, and a conveying roller 29 located below the structure moving along the conveying path F1. Each of the guide roller 28 and the conveying roller 29 is formed of a metal such as iron or stainless steel.

[0019] Next, the slurry coating step S1 and the first drying step S2 will be described in detail.

[0020] First, a slurry containing at least one of a niobium-containing oxide and a titanium-containing oxide and water is supplied to the slurry storage section 23. The slurry is prepared, for example, by dispersing at least one of a niobium-containing oxide and a titanium-containing oxide, a conductive agent, and a binder in a water-containing solvent. The active material, the conductive agent, the binder, and the solvent will be described later. The slurry supplied to the slurry storage section 23 is supplied to the first die coater 24 and the second die coater 25 by a slurry supply passage. The current collector 3a sent out from the current collector roll 26 moves along the transport path F1, and in the first die coater 24, the slurry is coated (applied) on one side of the current collector 3a, except for both ends perpendicular to the transport direction (longitudinal direction). The current collector (structure) with the slurry applied on one side moves along the transport path F1, is introduced into the drying furnace 21 from its entrance, and is subjected to a first drying S2 in the drying furnace 21, after which it is discharged from the exit of the drying furnace 21 and taken up by the take-up roller 27. As a result, the structure is wound into a roll.

[0021] Next, the uncoated surface (the other side) of the current collector 3a is unwound from the roll-shaped structure, and the uncoated surface of the current collector 3a is coated (applied) with the slurry by the second die coater 25, except for both ends perpendicular to the conveying direction (longitudinal direction). This completes the slurry application S1. The current collector (structure) with the slurry coated on the remaining side moves along the conveying path F1, is introduced into the drying furnace 21 from the entrance of the drying furnace 21, is subjected to the first drying S2 in the drying furnace 21, and is then discharged from the exit of the drying furnace 21 and taken up by the take-up roller 27. This completes the first drying S2.

[0022] In the structure 10 shown in Figs. 3 to 5, the region where the slurry is applied to form an active material-containing layer is indicated as 3b, and the region where the slurry is not applied and no active material-containing layer exists is indicated as 3a. The region 3b of the structure where the slurry is applied shrinks in the short side direction due to drying in the drying furnace 21. On the other hand, both end portions 3a perpendicular to the transport direction (longitudinal direction) of the structure are not applied with the slurry, and therefore hardly shrink due to drying. Due to the stress difference caused by this phenomenon, the end portions where the active material-containing layer is not formed tend to bend. The direction of the force that tries to bend is indicated by the reference symbol 30 in Fig. 2.

[0023] After the slurry is applied, the active material-containing non-forming parts at both ends of the structure are moved to the take-up roller 27 along the transport path F1 while being sandwiched between the guide roller 28 and the transport roller 29, as shown in Figs. 6 and 7. As a result, the structure can be moved along the transport path F1 while being stretched in a direction (short direction) perpendicular to the transport direction (longitudinal direction), so that curvature due to drying of the slurry can be suppressed. Note that Fig. 7 shows an example in which the active material-containing layer 3b is formed on both sides of the current collector 3a, but after the curvature correction is performed by the guide roller 28 and the transport roller 29 at the stage of forming the active material-containing layer 3b on one side of the current collector 3a, the curvature correction may be performed again by the guide roller 28 and the transport roller 29 when the active material-containing layer 3b is formed on the other side of the current collector 3a. Fig. 8 shows an example of a roll 31 of the structure wound by the winding roller 27. In Fig. 8, the winding core located at the winding center of the roll 31 of the structure is omitted.

[0024] Here, the first drying is performed so that an active material-containing layer having a moisture content of 1000 ppm by mass or more and 10000 ppm by mass or less as measured by the Karl Fischer method is formed from the dried slurry. A method for measuring the moisture content by the Karl Fischer method will be described. Samples (including a current collector) having a size of 3 mm x 2 cm are cut out from each of the short sides at the beginning and end of the roll 31 of the structure. The two prepared samples are prevented from drying before the moisture content is measured. Specifically, for example, after the samples are prepared, they are placed in a sealed container and taken to a measuring device. Alternatively, the samples are prepared at a location where a measuring device is located, and the measurement is immediately performed on the spot.

[0025] The moisture content of each of the two samples prepared as described above is measured by coulometric titration using a Karl Fischer moisture meter (VA-06, manufactured by Mitsubishi Chemical Analytech Co., Ltd.). Specifically, the sample is heated to 140°C and nitrogen gas is introduced at a flow rate of 200 ml / min. The moisture content is calculated from the amount of electricity consumed in the reaction between water and iodine. The average of the two moisture contents obtained is regarded as the moisture content of the active material-containing layer by the Karl Fischer method.

[0026] The short side of the structure at the start of winding may be, for example, the short side where the structure emerges from the outlet after passing through a drying oven, whereas the short side of the structure at the end of winding may be, for example, the position where the head is released after coating is completed.

[0027] By making the moisture content of the active material-containing layer 1000 mass ppm or more by the Karl Fischer method, it is possible to suppress the occurrence of breakage and chipping in the structure during pressing performed after drying. By making the moisture content 10000 mass ppm or less, it is possible to prevent defects during pressing, such as the slurry adhering to the press roller during pressing. The more preferable range of the moisture content is 1500 mass ppm or more and 5000 mass ppm or less.

[0028] The drying temperature of the slurry can be in the range of 25°C or more and 100°C or less, and more preferably 25°C or more and less than 80°C. By setting the drying temperature in the range of 25°C or more and 100°C or less, it is possible to remove the moisture in the material constituting the active material-containing layer while leaving a predetermined amount of moisture. When the temperature is 25°C or more and less than 80°C, the drying time can be, for example, in the range of 10 seconds or more and 600 seconds or less. More preferably, it is 60 seconds or more and 240 seconds or less. Here, the drying temperature is, for example, the temperature inside the drying furnace 21. The water content of the active material-containing layer as determined by the Karl Fischer method can be adjusted, for example, by the drying temperature, drying time, composition of the active material-containing layer, and the like.

[0029] The structure 10 that has been subjected to the first drying S2 is wound up by a winding roller 27. Moisture-containing structures may come into contact with each other and transfer unevenness to each other. By adjusting the winding tension according to the moisture content of the active material-containing layer of the structure 10, it is possible to avoid the phenomenon of transfer, in which the active material-containing layer is compressed and unevenness occurs on the surface. The winding tension can be set, for example, in the range of 5 N to 30 N.

[0030] The coating S1 and the first drying S2 may be performed on one side of the current collector or on both sides of the current collector at the same time. For example, the slurry is applied to one side of the current collector, and then the drying conditions of the slurry are adjusted to form an active material-containing layer containing moisture of 1000 ppm by mass to 10000 ppm by mass as measured by the Karl Fischer method. The slurry is then applied to the other side of the current collector, and the slurry is dried by the same drying method to obtain a current collector (structure) on which an active material-containing layer containing moisture of 1000 ppm by mass to 10000 ppm by mass as measured by the Karl Fischer method is formed. The application and drying of the slurry to the other side of the current collector may also be omitted.

[0031] Next, the press S3 will be described. An example of a device used in the press S3 is shown in Figs.

[0032] The manufacturing apparatus 32 of the example of FIG. 9 includes a rolling section and a winding section 40. In the manufacturing apparatus 32, the structure 10 in which the active material-containing layer 3b has been dried is carried into the rolling section. The conveying direction is indicated by F1. Then, the structure 10 is conveyed from the rolling section to the winding section 40 through guide rollers 35 to 39 in this order. The winding section 40 winds up the conveyed structure 10. In the example of FIG. 9, the winding section 40 includes a winding reel, and the structure 10 is wound up in a roll on the winding reel. In the example of FIG. 9, the structure 10 is guided from the upstream side to the downstream side by five guide rollers 35, 36, 37, 38, and 39 between the rolling section and the winding section 40. Each of the guide rollers 35 to 39 is formed of a metal such as iron or stainless steel.

[0033] The rolling section rolls the active material-containing layer 3b in the transported structure 10 by a roll press or the like. As shown in FIG. 9 and FIG. 10, the rolling section includes a pair of press rollers 33, 34, each of which is made of a metal such as iron or stainless steel. The press roller 33 presses the active material-containing layer 3b from one side in the thickness direction of the structure 10, and the press roller 34 presses the active material-containing layer 3b from the opposite side to the press roller 33 in the thickness direction of the structure 10. As a result, the active material-containing layer 3b is sandwiched between the press rollers 33, 34 in the thickness direction of the structure 10, and pressure (press pressure) in the thickness direction of the structure 10 is applied to the active material-containing layer 3b. At this time, when the active material-containing layer 3b is applied to both sides of the current collector 3a, the active material-containing layer 3b is pressed in a state in which each of the press rollers 33, 34 is in contact with the active material-containing layer 3b. When the active material-containing layer 3b is applied to only one surface of the current collector 3a, the active material-containing layer 3b is pressed with one of the press rollers 33, 34 in contact with the active material-containing layer 3b and the other of the press rollers 33, 34 in contact with the coated region of the current collector 3a. The pressure from the press rollers 33, 34 compresses the active material-containing layer 3b in the thickness direction of the structure 10 and stretches it in the longitudinal direction of the structure 10.

[0034] The rolled structure is wound up by the winding section 40. At this time, a winding tension is applied to the structure 10. Since the surface of the rolled structure is smooth, even if the winding tension is increased, a flat electrode can be formed without transferring unevenness between the two. Furthermore, when the moisture content of the structure is low, it is desirable to reduce the tensile stress in order to avoid breakage. The winding tension can be adjusted in the range of 10N or more and 100N or less. To suppress wrinkles during pressing, it is preferable to apply a winding tension of 30N or more.

[0035] Next, cutting S4 will be described.

[0036] The structure wound into a roll in the previous step is sent out and cut into a predetermined shape by punching with a punching die as shown in FIG. 11. In FIG. 11, the cut sides are indicated by dotted lines. In this way, an electrode 3 having a structure as shown in FIG. 12, for example, is obtained. As shown in FIG. 12, the electrode 3 comprises a rectangular current collector 3a, active material-containing layers 3b provided on both main surfaces of the current collector 3a, and a current collector tab 3c protruding in a rectangular shape from one end of the current collector 3a. The current collector tab 3c is obtained by punching out a portion of the current collector 3a where the active material-containing layer is not formed into a predetermined shape.

[0037] An example of cutting using a punching die is cutting (punching) using a Thomson blade.

[0038] 13 shows an example of an electrode of Comparative Example 3 in which wrinkles 41 were generated in the current collecting tab 3c near the active material-containing layer 3b during pressing. Details of Comparative Example 3 will be described later. According to the method of the embodiment, the electrode is unlikely to break even when a large tension is applied during pressing, so that it is possible to prevent wrinkles from being generated in the tab portion.

[0039] It should be noted that cutting S4 is for obtaining a predetermined shape, and therefore can be omitted if the predetermined shape is obtained in the steps up to S3.

[0040] The electrode manufactured by the method of the embodiment will be described in detail below.

[0041] The electrode may include a current collector and an active material-containing layer. The active material-containing layer may be laminated or formed on one or both sides of the current collector. The active material-containing layer may include an active material and, optionally, a conductive agent and a binder.

[0042] The electrodes can be used as positive or negative electrodes.

[0043] The active material includes at least one of a niobium-containing oxide and a titanium-containing oxide. Examples of the niobium-containing oxide include a monoclinic niobium-containing oxide and a niobium titanium-containing oxide. Examples of the monoclinic niobium-containing oxide include Nb2TiO7, Nb2Ti2O9, and Nb 10 Ti2O 29 , Nb 14 TiO 37 , Nb 24 TiO 62 The niobium titanium-containing oxide may be a substituted niobium titanium composite oxide in which at least a part of Nb and / or Ti is substituted with a different element. Examples of the substituted element include Na, K, Ca, Co, Ni, Si, P, V, Cr, Mo, Ta, Zr, Mn, Fe, Mg, B, Pb, and Al. The substituted niobium titanium composite oxide may contain one type of substituted element, or may contain two or more types of substituted elements. The active material particles may contain one type of niobium-containing oxide, or may contain multiple types of niobium-containing oxide. The niobium-containing oxide preferably contains Nb2TiO7 having a monoclinic structure. In this case, an electrode having excellent capacity and rate performance can be obtained.

[0044] Examples of monoclinic niobium titanium oxides include Li x Ti 1-y M1 y Nb 2-z M2 z O 7+δHere, M1 is at least one selected from the group consisting of Zr, Si, and Sn. M2 is at least one selected from the group consisting of V, Ta, and Bi. The subscripts in the composition formula are 0≦x≦5, 0≦y<1, 0≦z<2, and -0.3≦δ≦0.3.

[0045] Other examples of monoclinic niobium titanium oxides include Ti 1-y M3 y+z Nb 2-z O 7-δ Here, M3 is at least one selected from Mg, Fe, Ni, Co, W, Ta, and Mo. The subscripts in the composition formula are 0≦y<1, 0≦z<2, and -0.3≦δ≦0.3.

[0046] Another example of a monoclinic niobium titanium oxide is Li a TiM b Nb 2±β O 7±σ (0≦a≦5, 0≦b≦0.3, 0≦β≦0.3, 0≦σ≦0.3, M is at least one element selected from the group consisting of Fe, V, Mo and Ta).

[0047] The niobium-containing oxide may contain unavoidable impurities, examples of which include K, Na, Si, and P.

[0048] The niobium-containing oxide may contain lithium ions by charging, or may be synthesized as a niobium-containing oxide containing lithium by using a compound containing lithium such as lithium carbonate as a starting material for the niobium-containing oxide.

[0049] Titanium-containing oxides include, for example, titanium dioxide with a monoclinic structure, titanium dioxide with a rutile structure, and titanium dioxide with an anatase structure. Titanium dioxide with each crystal structure has a composition of TiO2 before charging and a composition of LiO2 after charging. xIt can be expressed as TiO2 (x is 0≦x≦1). In addition, the structure of titanium dioxide with a monoclinic crystal structure before charging can be expressed as TiO2(B).

[0050] The titanium-containing oxide may contain unavoidable impurities, such as K, Na, Cs, Ba, Ca, Si, and P.

[0051] The niobium-containing oxide and the titanium-containing oxide desirably do not contain lithium when mixed with a solvent containing water to be described later and contained in a slurry, which prevents the slurry from becoming alkaline, thereby suppressing deterioration of the current collector.

[0052] The type of active material used may be one or more. The active material may also contain a second active material other than the niobium-containing oxide and the titanium-containing oxide. An example of the second active material is lithium titanate having a ramsdellite structure (e.g., Li 2+y Ti3O7, 0≦y≦3), lithium titanates with spinel structure (e.g., Li 4+x Ti5O 12 , 0≦x≦3), hollandite-type titanium composite oxide, and orthorhombic titanium composite oxide.

[0053] The active material may be in the form of particles, which may be, for example, primary particles alone, secondary particles formed by agglomeration of primary particles, or a mixture of primary particles and secondary particles.

[0054] The conductive agent is blended to improve the current collecting performance and to reduce the contact resistance between the active material and the current collector. Examples of the conductive agent include vapor grown carbon fiber (VGCF), carbon nanotubes, carbon black such as acetylene black, and carbonaceous materials such as graphite. One of these may be used as the conductive agent, or two or more may be used in combination as the conductive agent. Alternatively, instead of using a conductive agent, a carbon coating or an electronically conductive inorganic material coating may be applied to the surface of the active material particles.

[0055] The binder can fill the gaps between the active material and can bind the active material and the current collector. The binder has affinity with the water-containing solvent and can be dispersed or dissolved in the water-containing solvent. Examples of the binder include carboxymethyl cellulose (CMC) and a salt of CMC. Examples of the salt of CMC include a sodium salt of CMC and a potassium salt of CMC. One of these may be used as the binder, or two or more may be used in combination as the binder. The binder containing CMC and / or a salt of CMC can cover the surface of the niobium-containing oxide particles, and therefore can suppress the reaction between the niobium-containing oxide particles and the electrolyte.

[0056] Styrene-butadiene rubber may be added to the binder containing CMC and / or a salt of CMC, thereby improving the binding strength between the active material-containing layer and the current collector.

[0057] The water-containing solvent may be water alone or a polar solvent containing water.

[0058] The active material-containing layer may contain a solid electrolyte. The lithium ion conductivity of the solid electrolyte is, for example, 1×10 -6 Scm -1 Examples of the lithium ion conductive solid electrolyte include a lithium ion conductive oxide-based solid electrolyte and a lithium ion conductive sulfide-based solid electrolyte. Examples of the lithium ion conductive oxide-based solid electrolyte include a lithium phosphate solid electrolyte with a NASICON structure, an amorphous LIPON (Li 2.9 PO 3.3 N 0.46 ), or garnet-type structure LLZ (Li7La3Zr2O 12 ) etc.

[0059] As an example, the active material, conductive agent, and binder in the active material-containing layer are preferably mixed in proportions of 68% by mass or more and 96% by mass or less, 2% by mass or more and 30% by mass or less, and 2% by mass or more and 30% by mass or less, respectively. By making the amount of conductive agent 2% by mass or more, the current collection performance of the active material-containing layer can be improved. Also, by making the amount of binder 2% by mass or more, the binding between the active material-containing layer and the current collector becomes sufficient, and excellent cycle performance can be expected. On the other hand, it is preferable to make the conductive agent and binder 30% by mass or less each in order to increase capacity.

[0060] The current collector is made of a material that is electrochemically stable at the potential at which lithium (Li) is inserted into and extracted from the active material. One example of the current collector is copper, nickel, stainless steel, or aluminum, or an aluminum alloy containing one or more elements selected from Mg, Ti, Zn, Mn, Fe, Cu, and Si. The thickness of the current collector is preferably 5 μm or more and 20 μm or less. A current collector having such a thickness can balance the strength and weight of the electrode.

[0061] The current collector may also include a portion on the surface of which no active material-containing layer is formed, and this portion can function as a current collecting tab.

[0062] According to the first embodiment described above, there is provided a method for producing an electrode, including a step of obtaining a structure by applying a slurry containing at least one of a niobium-containing oxide and a titanium-containing oxide and water to a current collector, a step of drying the slurry to form an active material-containing layer having a water content of 1000 ppm by mass or more and 10000 ppm by mass or less as measured by the Karl Fischer method, and a step of pressing the structure.

[0063] According to the first embodiment, at least when pressing and cutting are performed, it is possible to suppress the occurrence of breakage and chipping in the structure due to pressing and cutting. Second embodiment The second embodiment relates to a method for manufacturing a battery.

[0064] The second embodiment includes a step of preparing an electrode group by using the electrode obtained by the method of the first embodiment as a first electrode and disposing a separator between the first electrode and a second electrode; A step of housing the electrode group in an exterior member; and retaining a non-aqueous electrolyte in the electrode group housed in the exterior member.

[0065] The method of the second embodiment includes steps S5 to S8 shown in FIG.

[0066] The electrode group preparation step S5 will now be described.

[0067] The electrode group is produced, for example, by disposing a separator between a first electrode and a second electrode. The shape of the electrode group is not particularly limited, and may be, for example, a stack of the first electrode, the separator, and the second electrode, a flat or cylindrically wound first electrode, a zigzag first electrode, the separator, and the second electrode, or the like.

[0068] The second electrode and the separator will now be described.

[0069] The second electrode may include a second current collector and a second active material-containing layer. The second active material-containing layer may be formed on one or both sides of the second current collector. The second active material-containing layer may include a second active material, and optionally a conductive agent and a binder. The second electrode may be a positive electrode or a negative electrode, but when the first electrode is a negative electrode, it may be a positive electrode.

[0070] The second active material may be, for example, an oxide or a sulfide. The second electrode may contain, as the active material, one type of compound alone or two or more types of compounds in combination. Examples of oxides and sulfides include compounds that can insert and remove Li or Li ions.

[0071] Examples of such compounds include manganese dioxide (MnO2), iron oxide, copper oxide, nickel oxide, lithium manganese composite oxides (e.g., Li x Mn2O4 or Li x MnO2; 0 < x ≦ 1), lithium nickel composite oxides (e.g., Li x NiO2; 0 < x ≦ 1), lithium cobalt composite oxides (e.g., Li x CoO2; 0 < x ≦ 1), lithium nickel cobalt composite oxides (e.g., Li x Ni 1-y Co y O2; 0 < x ≦ 1, 0 < y < 1), lithium manganese cobalt composite oxides (e.g., Li x Mn y Co 1-y O2; 0 < x ≦ 1, 0 < y < 1), lithium manganese nickel composite oxides having a spinel structure (e.g., Li x Mn 2-y Ni y O4; 0 < x ≦ 1, 0 < y < 2), lithium phosphate oxides having an olivine structure (e.g., Li x FePO4; 0 < x ≦ 1, Li x Fe 1-y Mn y PO4; 0 < x ≦ 1, 0 < y ≦ 1, Li x CoPO4; 0 < x ≦ 1), iron sulfate (Fe2(SO4)3), vanadium oxides (e.g., V2O5), LiNi x Co y M z O2 (x + y + z = 1, x ≧ 0.8, M consists of Mn and Al), and lithium nickel cobalt manganese composite oxides (Li x Ni 1-y-z Co y Mn z O2; 0 < x ≦ 1, 0 < y < 1, 0 < z < 1, y + z < 1) are included.

[0072] The primary particle size of the second active material is preferably 100 nm or more and 1 μm or less. The second active material with a primary particle size of 100 nm or more is easy to handle in industrial production. The second active material with a primary particle size of 1 μm or less can smoothly progress the solid-state diffusion of lithium ions.

[0073] The specific surface area of ​​the second active material is 0.1 m 2 / g or more 10m 2 / g or less. 2 The second active material having a specific surface area of ​​10 m 2 A second active material having a specific surface area of ​​100 / g or less is easy to handle in industrial production and can ensure good charge-discharge cycle performance.

[0074] The binder is blended to fill the gaps of the dispersed second active material and to bind the second active material and the second current collector. Examples of the binder include polytetrafluoroethylene (PTFE), polyvinylidene fluoride (PVdF), fluorine-based rubber, polyacrylic acid compounds, imide compounds, carboxymethylcellulose (CMC), and salts of CMC. One of these may be used as the binder, or two or more may be used in combination as the binder.

[0075] The conductive agent is blended to improve current collection performance and reduce contact resistance between the second active material and the second current collector. Examples of the conductive agent include vapor grown carbon fiber (VGCF), carbon black such as acetylene black, and carbonaceous materials such as graphite. One of these may be used as the conductive agent, or two or more may be used in combination as the conductive agent. The conductive agent may also be omitted.

[0076] In the second active material-containing layer, the second active material and the binder are preferably mixed in an amount of 80% by mass or more and 98% by mass or less and 2% by mass or more and 20% by mass or less, respectively.

[0077] By making the amount of binder 2% by mass or more, sufficient electrode strength can be obtained. In addition, the binder can function as an insulator. Therefore, by making the amount of binder 20% by mass or less, the amount of insulator contained in the electrode is reduced, and the internal resistance can be reduced.

[0078] When a conductive agent is added, the second active material, binder, and conductive agent are preferably mixed in proportions of 77% by mass or more and 95% by mass or less, 2% by mass or more and 20% by mass or less, and 3% by mass or more and 15% by mass or less, respectively.

[0079] By setting the amount of the conductive agent to 3% by mass or more, the above-mentioned effects can be achieved. Also, by setting the amount of the conductive agent to 15% by mass or less, the ratio of the conductive agent in contact with the electrolyte can be reduced. If this ratio is low, decomposition of the electrolyte during high-temperature storage can be reduced.

[0080] The second current collector is preferably an aluminum foil or an aluminum alloy foil containing one or more elements selected from Mg, Ti, Zn, Ni, Cr, Mn, Fe, Cu and Si.

[0081] The thickness of the aluminum foil or aluminum alloy foil is preferably 5 μm or more and 20 μm or less, more preferably 15 μm or less. The purity of the aluminum foil is preferably 99% by mass or more. The content of transition metals such as iron, copper, nickel, and chromium contained in the aluminum foil or aluminum alloy foil is preferably 1% by mass or less.

[0082] The second current collector may also include a portion on the surface of which the second active material-containing layer is not formed, and this portion may function as a second current collecting tab.

[0083] For example, the second electrode is prepared by suspending the second active material, the conductive agent, and the binder in a solvent to prepare a slurry. The slurry is then applied to one or both sides of a current collector. The applied slurry is then dried to obtain a laminate of an active material-containing layer and a current collector. Then, the laminate is pressed. In this manner, the second electrode is prepared. Alternatively, the second electrode may be prepared by the following method. First, the active material, the conductive agent, and the binder are mixed to obtain a mixture. Then, the mixture is formed into pellets. Then, the pellets are placed on the current collector to obtain the second electrode.

[0084] The separator is formed, for example, from a porous film containing polyethylene (PE), polypropylene (PP), cellulose, or polyvinylidene fluoride (PVdF), or a synthetic resin nonwoven fabric. From the viewpoint of safety, it is preferable to use a porous film formed from polyethylene or polypropylene. This is because these porous films melt at a certain temperature and are capable of cutting off electric current.

[0085] The separator may be an electrolyte layer containing a solid electrolyte. The lithium ion conductivity of the solid electrolyte is, for example, 1x10 -6 Scm -1 Examples of the lithium ion conductive solid electrolyte include a lithium ion conductive oxide-based solid electrolyte and a lithium ion conductive sulfide-based solid electrolyte. Examples of the lithium ion conductive oxide-based solid electrolyte include a lithium phosphate solid electrolyte with a NASICON structure, an amorphous LIPON (Li 2.9 PO 3.3 N 0.46 ), or garnet-type structure LLZ (Li7La3Zr2O 12 ) etc.

[0086] Next, step S6 of housing the electrode group in an exterior member will be described.

[0087] The electrode group is housed in an exterior member. The exterior member is not sealed and is left in an open state. Before the housing, current collecting leads may be electrically connected to the first electrode and the second electrode of the electrode group.

[0088] As the exterior member, for example, a container made of a laminate film or a metal container can be used.

[0089] The thickness of the laminate film is, for example, 0.5 mm or less, preferably 0.2 mm or less.

[0090] The laminate film is a multi-layer film including a plurality of resin layers and a metal layer interposed between the resin layers. The resin layers include polymeric materials such as polypropylene (PP), polyethylene (PE), nylon, and polyethylene terephthalate (PET). The metal layer is preferably made of aluminum foil or aluminum alloy foil for weight reduction. The laminate film can be molded into the shape of the exterior member by sealing it by heat fusion.

[0091] The thickness of the wall of the metal container is, for example, 1 mm or less, more preferably 0.5 mm or less, and even more preferably 0.2 mm or less.

[0092] The metal container is made of, for example, aluminum or an aluminum alloy. The aluminum alloy preferably contains elements such as magnesium, zinc, and silicon. When the aluminum alloy contains transition metals such as iron, copper, nickel, and chromium, the content of the transition metals is preferably 100 ppm by mass or less.

[0093] The shape of the exterior member is not particularly limited. The shape of the exterior member may be, for example, flat (thin), rectangular, cylindrical, coin, or button. The exterior member can be appropriately selected depending on the battery dimensions and the application of the battery.

[0094] The current collecting lead can be formed, for example, from a conductive material, such as the same type of material as the current collector of the electrode or the current collector of the second electrode.

[0095] The electrode group housed in the exterior member may be dried at a temperature of 80° C. or more and 150° C. or less. The drying step is carried out on the exterior member while it is still unsealed.

[0096] By setting the drying temperature in the range of 80° C. to 150° C., it is possible to remove moisture contained in the electrode group without thermally deteriorating the materials contained in the electrode group. When the drying temperature is 80° C. to 150° C., the drying time can be, for example, 1 hour to 72 hours.

[0097] Next, step S7 of housing the electrolyte in the exterior member will be described.

[0098] The electrolyte is retained in the electrode group while the exterior member is left in an open state. The retaining step is carried out, for example, in a dehumidified atmosphere or in dry air.

[0099] Examples of the electrolyte include non-aqueous electrolytes and aqueous electrolytes. For example, liquid non-aqueous electrolytes or gel non-aqueous electrolytes can be used as the non-aqueous electrolyte. The liquid non-aqueous electrolyte is prepared by dissolving an electrolyte salt as a solute in an organic solvent. The concentration of the electrolyte salt is preferably 0.5 mol / L or more and 2.5 mol / L or less.

[0100] Examples of the electrolyte salt include lithium salts such as lithium perchlorate (LiClO4), lithium hexafluorophosphate (LiPF6), lithium tetrafluoroborate (LiBF4), lithium hexafluoroarsenate (LiAsF6), lithium trifluoromethanesulfonate (LiCF3SO3), and lithium bistrifluoromethylsulfonylimide (LiN(CF3SO2)2), and mixtures thereof. The electrolyte salt is preferably one that is difficult to oxidize even at high potentials, and LiPF6 is most preferred.

[0101] Examples of organic solvents include cyclic carbonates such as propylene carbonate (PC), ethylene carbonate (EC), and vinylene carbonate (VC); chain carbonates such as diethyl carbonate (DEC), dimethyl carbonate (DMC), and methyl ethyl carbonate (MEC); cyclic ethers such as tetrahydrofuran (THF), 2-methyl tetrahydrofuran (2MeTHF), and dioxolane (DOX); chain ethers such as dimethoxyethane (DME) and diethoxyethane (DEE); γ-butyrolactone (GBL), acetonitrile (AN), and sulfolane (SL). These organic solvents can be used alone or as a mixed solvent.

[0102] The gelled non-aqueous electrolyte is prepared by combining a liquid non-aqueous electrolyte with a polymeric material, such as polyvinylidene fluoride (PVdF), polyacrylonitrile (PAN), polyethylene oxide (PEO), or a mixture thereof.

[0103] Alternatively, as the nonaqueous electrolyte, in addition to liquid nonaqueous electrolytes and gel nonaqueous electrolytes, room temperature molten salts containing lithium ions (ionic melts), polymer solid electrolytes, inorganic solid electrolytes, and the like may be used.

[0104] Room temperature molten salts (ionic melts) refer to organic salts consisting of a combination of organic cations and anions that can exist as a liquid at room temperature (15°C or higher and 25°C or lower). Room temperature molten salts include room temperature molten salts that exist as a liquid by themselves, room temperature molten salts that become liquid when mixed with an electrolyte salt, room temperature molten salts that become liquid when dissolved in an organic solvent, and mixtures of these. In general, the melting point of room temperature molten salts used in secondary batteries is 25°C or lower. In addition, organic cations generally have a quaternary ammonium skeleton.

[0105] The polymer solid electrolyte is prepared by dissolving an electrolyte salt in a polymer material and solidifying it.

[0106] The inorganic solid electrolyte is a solid substance having Li-ion conductivity. The lithium ion conductivity of the solid electrolyte is, for example, 1x10 at 25°C. -6 Scm -1 Examples of the lithium ion conductive solid electrolyte are as described above.

[0107] Next, sealing S8 will be described.

[0108] The exterior member is sealed to obtain a battery. The sealing method varies depending on the type of exterior member. For example, in the case of a container made of a laminate film, heat sealing can be used. In addition, in the case of a metal container, laser welding can be used.

[0109] Examples of batteries that can be manufactured by the method according to the embodiment are shown in FIGS.

[0110] 14 and 15 show examples of batteries equipped with a stacked electrode group.

[0111] 14 and 15 includes an electrode group 1 shown in Fig. 14 and 15, an exterior member 2 shown in Fig. 14, and a non-aqueous electrolyte (not shown). The electrode group 1 and the non-aqueous electrolyte are housed in the exterior member 2. The non-aqueous electrolyte is held in the electrode group 1.

[0112] The exterior member 2 is made of a laminate film including two resin layers and a metal layer interposed between them.

[0113] The electrode group 1 is a laminated type electrode group, as shown in Fig. 15. The laminated type electrode group 1 has a structure in which negative electrodes 3 and positive electrodes 5 are alternately laminated with separators 4 interposed therebetween.

[0114] The electrode group 1 includes a plurality of negative electrodes 3. Each of the plurality of negative electrodes 3 includes a negative electrode current collector 3a and a negative electrode active material-containing layer 3b supported on both sides of the negative electrode current collector 3a. The electrode group 1 also includes a plurality of positive electrodes 5. Each of the plurality of positive electrodes 5 includes a positive electrode current collector 5a and a positive electrode active material-containing layer 5b supported on both sides of the positive electrode current collector 5a.

[0115] The negative electrode current collector 3a of each negative electrode 3 includes a portion 3c on one side of which the negative electrode active material-containing layer 3b is not supported on any surface. This portion 3c serves as a negative electrode current collector tab. The portion 3c serving as a negative electrode current collector tab does not overlap with the positive electrode 5. In addition, the multiple negative electrode current collector tabs (portions 3c) are electrically connected to a strip-shaped negative electrode terminal 6. The tip of the strip-shaped negative electrode terminal 6 is pulled out to the outside of the exterior member 2.

[0116] Although not shown, the positive electrode current collector 5a of each positive electrode 5 includes a portion on one side where the positive electrode active material-containing layer 5b is not supported on any surface. This portion serves as a positive electrode current collector tab. The positive electrode current collector tab does not overlap with the negative electrode 3, similar to the negative electrode current collector tab (portion 3c). The positive electrode current collector tab is located on the opposite side of the electrode group 1 to the negative electrode current collector tab (portion 3c). The positive electrode current collector tab is electrically connected to a strip-shaped positive electrode terminal 7. The tip of the strip-shaped positive electrode terminal 7 is located on the opposite side to the negative electrode terminal 6, and is drawn out to the outside of the exterior member 2.

[0117] The laminated electrode group is not limited to the structure shown in FIG. 15. Another example of the laminated electrode group 1 is shown in FIG. 16. A positive electrode 5, a negative electrode 3, a positive electrode 5, and a negative electrode 3 are arranged in this order so as to be sandwiched between the separators 4 folded in a zigzag pattern. A positive electrode current collecting tab 5c protrudes from one long side of the separator 4 folded in a zigzag pattern. A negative electrode current collecting tab (not shown) protrudes from the other long side of the separator 4 folded in a zigzag pattern. The order of the positive electrode 5 and the negative electrode 3 is not limited to that shown in FIG. 15, and may be the negative electrode 3 and the positive electrode 5.

[0118] 17 and 18 show examples of batteries equipped with a wound type electrode group.

[0119] 17 and 18 includes a bag-shaped exterior member 2 shown in Fig. 17 and 18, an electrode group 1 shown in Fig. 17, and an electrolyte (not shown). The electrode group 1 and the non-aqueous electrolyte are housed in the bag-shaped exterior member 2. The non-aqueous electrolyte (not shown) is held in the electrode group 1.

[0120] The bag-shaped exterior member 2 is made of a laminate film including two resin layers and a metal layer interposed between them.

[0121] As shown in Fig. 17, the electrode group 1 is a flat wound-type electrode group. As shown in Fig. 18, the flat wound-type electrode group 1 includes a negative electrode 3, a separator 4, and a positive electrode 5. The separator 4 is interposed between the negative electrode 3 and the positive electrode 5.

[0122] The negative electrode 3 includes a negative electrode current collector 3a and a negative electrode active material-containing layer 3b. In the negative electrode 3, in a portion located at the outermost shell of the wound-type electrode group 1, the negative electrode active material-containing layer 3b is formed only on the inner surface side of the negative electrode current collector 3a as shown in Fig. 18. In the other portions of the negative electrode 3, the negative electrode active material-containing layer 3b is formed on both sides of the negative electrode current collector 3a.

[0123] The positive electrode 5 includes a positive electrode current collector 5a and a positive electrode active material-containing layer 5b formed on both sides of the positive electrode current collector 5a.

[0124] As shown in FIG. 17, the negative electrode terminal 6 and the positive electrode terminal 7 are located near the outer peripheral end of the wound electrode group 1. The negative electrode terminal 6 is connected to a portion located at the outermost shell of the negative electrode current collector 3a. The positive electrode terminal 7 is connected to a portion located at the outermost shell of the positive electrode current collector 5a. The negative electrode terminal 6 and the positive electrode terminal 7 extend to the outside from an opening of the bag-shaped exterior member 2. A thermoplastic resin layer is provided on the inner surface of the bag-shaped exterior member 2, and the opening is closed by heat sealing.

[0125] The battery manufactured by the method of the second embodiment may be used as a battery pack or may be incorporated into a battery pack. The battery according to the embodiment is preferably used in applications requiring excellent cycle performance when a large current is drawn. Specifically, the battery is used as a power source for digital cameras, or as a vehicle battery for, for example, two- to four-wheeled hybrid electric vehicles, two- to four-wheeled electric vehicles, power-assisted bicycles, or railroad cars (e.g., trains), or as a stationary battery. In particular, the battery is preferably used as an on-board battery mounted on a vehicle.

[0126] According to the second embodiment described above, a battery is manufactured using the electrode manufactured by the method of the first embodiment. As a result, defects during electrode manufacturing can be reduced, and the yield of battery manufacturing can be improved. (Third embodiment) The third embodiment relates to a method for manufacturing an electrode.

[0127] The method of the third embodiment includes a second drying step in which the pressed structure of the method of the first embodiment is laminated in a thickness direction, and both sides of the obtained laminate intersecting the lamination direction are dried while being pressed, so that the moisture content of the active material-containing layer is 600 ppm by mass or less as measured by the Karl Fischer method.

[0128] An example of the third embodiment will be described with reference to FIGS.

[0129] The method of the third embodiment includes slurry coating S1, first drying S2, pressing S3, and second drying S9 shown in Fig. 19. The method of the third embodiment may also include cutting S4 shown in Fig. 19. Details of steps S1 to S4 and details of the electrodes are as described in the first embodiment. The second drying S9 will be described below.

[0130] In the second drying step S9, the structure (or electrode) after the pressing step S3 or the cutting step S4 is laminated in a thickness direction, and both sides of the laminate intersecting the lamination direction are pressed and dried to reduce the moisture content of the active material-containing layer to 600 ppm or less as measured by the Karl Fischer method. The second drying step will be described with reference to Figs. 20 and 21.

[0131] 20 and 21 show a jig used in the second drying. The housing 50 shown in FIG. 20 and FIG. 21 includes a container 51, a cover plate 52, a bottom plate 53, and a spring member 54. In FIG. 20 and FIG. 21, the long side direction of the container 51 is indicated as the y-axis direction, the short side direction of the container 51 is indicated as the x-axis direction, and the depth direction of the container 51 is indicated as the z-axis direction. The container 51 has a rectangular cylindrical shape with a bottom. The bottom plate 53 has planar dimensions that are the same or approximately the same as a plane along the xy axis surrounded by the inner wall of the container 51. The bottom plate 53 is disposed at a predetermined height in the z-axis direction from the bottom inner surface in the container 51. The spring member 54 is, for example, a coil spring. The spring member 54 is disposed between the bottom inner surface of the container 51 and the bottom plate 53. When the spring member 54 contracts, the position of the bottom plate 53 in the container 51 moves downward along the z-axis direction. Furthermore, when the spring member 54 expands, the position in the container 51 moves upward along the z-axis direction. A plurality of objects (for example, electrodes 3) to be subjected to the second drying S9 are prepared. A plurality of electrodes 3 are used in order to increase production efficiency. A plurality of electrodes 3 are stacked on the bottom plate 53 in the container 51 so that the thickness direction of the electrodes 3 is parallel to the depth direction (z-axis direction) of the container 51. The cover plate 52 is placed at the opening of the container 51. The upper end of the long side direction of the opening of the container 51 is bent inwardly, so that the cover plate 52 is fixed to the opening of the container 51. The stack of electrodes 3 is sandwiched between the cover plate 52 and the bottom plate 53. Furthermore, the stack of electrodes 3 receives an upward force along the z-axis direction due to the elastic force of the spring member 54 through the bottom plate 53. Therefore, the stack of electrodes 3 is sandwiched between the cover plate 52 and the bottom plate 53, and both sides are pressurized. This makes it possible to prevent deformation such as warping or curvature from occurring in electrode 3 during the second drying. Note that container 51, cover plate 52, and bottom plate 53 may be made of a metal such as Al or an Al alloy.

[0132] The housing 50 containing the laminate of the electrodes 3 described above is placed in a drying furnace and subjected to the second drying S9. The second drying S9 is performed so that the moisture content of the active material-containing layer 3b of the electrode 3 is 600 mass ppm or less by the Karl Fischer method. By making the moisture content 600 mass ppm or less, the hardness of the electrode 3 can be increased. This makes it possible to avoid manufacturing defects such as the electrode dropping, deformation, and inability to transport the electrode to a predetermined position when transporting the electrode to a later process. In addition, when the electrode 3 is used as the first electrode and a separator is placed between the first electrode and the second electrode to prepare an electrode group, it is possible to avoid the electrode being misaligned. As a result, the manufacturing yield can be improved. In addition, it is useful for improving the performance of a battery equipped with a non-aqueous electrolyte. The lower limit of the moisture content can be 50 mass ppm. By making the moisture content 50 ppm by mass or more, moisture can be left in the pores of the electrode, etc., which makes it possible to avoid thermal deterioration of the electrode components (e.g., the binder) and to prevent the electrode from becoming unnecessarily hard and brittle. The drying temperature in the second drying can be in the range of 80°C to 160°C, more preferably 100°C to 140°C. This allows the electrode to be dried to a suitable hardness, so that bending deformation when the electrode area is increased can be suppressed. The drying time can be in the range of, for example, 1 hour to 48 hours, more preferably 6 hours to 24 hours. Here, the drying temperature is, for example, the temperature inside the drying oven. The water content of the active material-containing layer as determined by the Karl Fischer method can be adjusted, for example, by the drying temperature, drying time, composition of the active material-containing layer, and the like. The second drying can be, for example, vacuum drying or reduced pressure drying.

[0133] A method for measuring the moisture content of the active material-containing layer 3b of the electrode 3 by the Karl Fischer method will be described below. After the second drying S9, the moisture content of each of the three electrodes 3 in the stack of electrodes 3 in the container 51, including the electrode 3 located in each of the outermost layers and the electrode 3 located in the center of the stack, is measured by the Karl Fischer method in the same manner as described in the first embodiment. The average of the three measured values ​​obtained is the value to be determined.

[0134] An electrode can be manufactured by a method including the steps described above.

[0135] According to the method of the third embodiment, the structure after pressing in the method of the first embodiment is laminated in a thickness direction, and both sides of the laminate intersecting the lamination direction are pressed while drying, thereby making the moisture content of the active material-containing layer 600 mass ppm or less by the Karl Fischer method. Therefore, in addition to being able to suppress the occurrence of breakage and chipping in the structure at least during pressing, the handling of the electrode during transportation is made easier, and the occurrence of defects during transportation can be reduced. Therefore, the manufacturing yield of the electrode can be improved. (Fourth embodiment) The fourth embodiment relates to a method for manufacturing a battery.

[0136] The fourth embodiment includes a step of preparing an electrode group by using the electrode obtained by the method of the third embodiment as a first electrode and disposing a separator between the first electrode and a second electrode; A step of housing the electrode group in an exterior member; and retaining a non-aqueous electrolyte in the electrode group housed in the exterior member.

[0137] The method of the fourth embodiment includes steps S5 to S8 shown in Fig. 19. The details of steps S5 to S8 and the details of the battery are the same as those described in the second embodiment. If the electrode group has reached an appropriate water content by the second drying step S9, the drying step in which the electrode group is housed in the exterior member described in the second embodiment may be omitted. This can shorten the tact time.

[0138] According to the fourth embodiment, since a battery is manufactured using the electrode obtained by the method of the third embodiment, it is possible to suppress the occurrence of breakage and chipping in the electrode structure at least during pressing. In addition, since the handling of the electrode during transportation becomes easier, the occurrence of defects during electrode transportation can be reduced. Furthermore, the occurrence of defects during the preparation of the electrode group can also be reduced. Therefore, the manufacturing yield of the battery can be improved. EXAMPLES

[0139] Examples will be described below. <Example 1> As the active material, particles of monoclinic niobium titanium-containing oxide having a composition represented by the formula TiNb2O7 were prepared. In addition, acetylene black was prepared as a conductive agent, and carboxymethyl cellulose and styrene butadiene rubber were prepared as binders. These were mixed in pure water so that the mass ratio of active material: acetylene black: carboxymethyl cellulose: styrene butadiene rubber was 90: 5: 2.5: 2.5 to obtain a slurry. This slurry was applied to one side of a belt-shaped current collector made of aluminum foil having a thickness of 12 μm, except for both ends in the short side direction, and the coating was dried for 300 seconds in a drying oven set at 70 ° C. During this first drying, drying was performed without applying guide rolls to both sides of the active material-containing layer non-forming part of the current collector.

[0140] The winding tension of the structure after one-side coating was adjusted to 10 N against the aluminum current collector. This makes it possible to prevent the semi-dried structures from transferring to each other. After one-side coating was completed, the slurry was applied to the uncoated side of the strip-shaped current collector in the same manner. Then, the slurry was dried (first drying) under the same conditions. The winding tension of the structure after coating was adjusted in the same manner. In this way, a structure was obtained with a length of 400 m in which an active material-containing layer was formed on both sides of the strip-shaped current collector except for both ends in the short side direction. The structure was also wound into a roll. The moisture content of the active material-containing layer of the structure was measured by the Karl Fischer method by the method described above, and the results are shown in Table 1. The coating amount of the active material-containing layer per side was 150 g / m 2 Next, the obtained structure was subjected to a test so that the density of the active material-containing layer was 2.65 g / cm 3 The electrode was subjected to roll pressing so that the initial tensile tension was 100N, and pressing was performed at a speed of 1m per minute. If breakage occurred during pressing, the tensile tension was reduced by 10N at a time, and the tension at which the electrode did not break per 100m of rolling distance was determined, and the electrode pressed at that tension was subjected to the next process. The tension during pressing is shown in Table 1 below.

[0141] The obtained electrode was punched out into 50 pieces in the electrode shape shown in FIG. 12 using a punching machine with a Thomson blade to prepare the electrode of Example 1. The electrode of Example 1 had a long side length of 80 mm, a short side length of 60 mm, and a current collecting tab width (width parallel to the short side direction of the active material containing layer) of 30 mm. The current collecting tab length (width parallel to the long side direction of the active material containing layer) was 10 mm. The outer periphery of the electrode of Example 1 was observed with a stereomicroscope, and electrodes in which cracks in the active material containing layer, cracks in the current collector, peeling of the active material containing layer, or deformation or peeling due to wrinkles in the current collecting tab were observed were determined to be defective cuts. The number of defective cuts is shown in Table 1. <Example 2> In the first drying step for drying the slurry, the active material-containing layer-free portions at both ends in the short side direction of the current collector of the structure were sandwiched between a guide roller 28 and a conveying roller 29 shown in FIG. 6 and dried. The tension during pressing was changed as shown in Table 1 below. Except for this, an electrode was manufactured in the same manner as in Example 1. The number of cutting defects was measured for the obtained electrode of Example 2 in the same manner as in Example 1, and the results are shown in Table 1. <Example 3> In the first drying step for drying the slurry, the active material-containing layer-free portions at both ends of the short side direction of the current collector of the structure were dried while being sandwiched between the guide roller 28 and the conveying roller 29 shown in FIG. 6. In addition, the drying temperature (temperature of the drying oven) of the slurry and the drying time were changed as shown in Table 1 below, and the moisture content of the active material-containing layer measured by the Karl Fischer method was changed as shown in Table 1 below. The tension during pressing was changed as shown in Table 1 below. Except for this, an electrode was manufactured in the same manner as in Example 1. The number of cutting defects was measured for the obtained electrode of Example 3 in the same manner as in Example 1, and the results are shown in Table 1. <Comparative Example 1 and Comparative Example 2> The drying temperature (temperature of the drying oven) of the slurry and the drying time were changed as shown in Table 1 below, and the moisture content of the active material-containing layer measured by the Karl Fischer method was changed as shown in Table 1 below. The tension during pressing was changed as shown in Table 1 below. Other than this, electrodes were produced in the same manner as in Example 1. The number of cutting defects was measured for the obtained electrodes of Comparative Example 1 and Comparative Example 2 in the same manner as in Example 1, and the results are shown in Table 1. <Comparative Example 3> The drying temperature (temperature of the drying oven) of the slurry and the drying time were changed as shown in Table 1 below, and the moisture content of the active material-containing layer as measured by the Karl Fischer method was changed as shown in Table 1 below. The tension during pressing was changed as shown in Table 1 below. In addition, after pressing, the active material-containing layer was humidified for 30 minutes in an environment with a dew point of 40° C., thereby changing the moisture content of the active material-containing layer as measured by the Karl Fischer method to 2000 ppm by mass. Except for this, an electrode was manufactured in the same manner as in Example 1. The number of cutting defects was measured for the obtained electrode of Comparative Example 3 in the same manner as in Example 1, and the results are shown in Table 1.

[0142] [Table 1]

[0143] As is clear from Table 1, in the method of Example 1, the electrodes were slightly curved because the guide roller was not used to straighten the curve during the first drying step. This made it difficult to apply tension to the electrodes during pressing, resulting in cutting defects at a rate of 1 out of 50 electrodes.

[0144] In the method of Example 2, the curvature was corrected by the guide roller during the first drying, so that the curvature was suppressed, and a tensile stress twice that of Example 1 could be applied during pressing, and cutting defects were eliminated.

[0145] In the method of Example 3, a flexible structure was obtained because the water content of the active material-containing layer was high. A tensile stress three times that of Example 1 could be applied during pressing, and cutting defects were eliminated.

[0146] As explained above, according to the method of the embodiment, since the active material-containing layer is pressed in a water-containing state, it is difficult to break even if a large tension is applied during pressing. The tension press can suppress the curvature of the electrode after pressing, and therefore the distortion of the coated and uncoated parts can be suppressed, which results in a reduction in poor cutting of the electrode. As in Examples 2 and 3, by correcting the curvature during drying of the slurry (first drying), the effect of suppressing poor cutting can be further enhanced.

[0147] On the other hand, according to the method of Comparative Example 1, the moisture content of the active material-containing layer was less than 1000 ppm by mass, so the structure was hard, curved, and press tension could not be applied, resulting in wrinkles. There were also many cutting defects. According to the method of Comparative Example 2, the moisture content of the active material-containing layer was more than 10000 ppm by mass, so the structure was too soft. Therefore, transfer between the active material-containing layers was unavoidable when winding after coating, and the application of press tension would cause breakage due to the unevenness of the transfer. If the tension was lowered to avoid breakage, wrinkles would occur. There were also many cutting defects. When humidifying after pressing, as in the method of Comparative Example 3, the active material-containing layer was hard and broke during pressing, so tension could not be applied and wrinkles occurred. No burrs or peeling were observed around the punched portion, but there were many wrinkles at the base of the tab, resulting in a high failure rate. In Comparative Example 1, the active material-containing layer was brittle due to the low moisture content, and press tension could not be applied. Therefore, the coated and uncoated parts of the electrode were significantly distorted, and cutting defects also occurred. If the number of defects is large, the time required for each good electrode is also long. In addition, in Comparative Example 3, the electrode was exposed to a dew point environment after pressing to absorb water, which made cutting defects less likely to occur, but because time was required for the electrode to absorb water and no pulling tension was applied during pressing, wrinkles occurred in the electrode tab area as shown in Figure 13, and good electrodes could not be obtained.

[0148] Therefore, according to the method of the embodiment, it is possible to improve tact time (production efficiency) and yield. <Example 4> 100 electrodes were prepared by the method of Example 1. These electrodes were used as negative electrodes. These negative electrodes were inserted into a container 51 of a case 50 shown in Figs. 20 and 21, sandwiched between a cover plate 52 and a bottom plate 53, and vacuum dried at 140°C for 12 hours. After drying, the moisture content of the negative electrodes located at the top and bottom outermost layers of the electrode stack and three negative electrodes located at the center was measured by the Karl Fischer method using the method described above, and the average value was calculated to be 350 ppm by mass.

[0149] Next, lithium cobalt oxide (LiCoO2) particles were prepared as the positive electrode active material. In addition, acetylene black was prepared as the conductive agent, and PVdF was prepared as the binder. These were dispersed in N-methyl-2-pyrrolidone (NMP) so that the mass ratio of active material: acetylene black: PVdF was 90:5:5 to obtain a slurry. This slurry was applied to both sides of a current collector made of 12 μm aluminum foil, and the coating was dried at 100° C. for 240 seconds. In this way, a laminate in which an active material-containing layer was formed on both sides of the current collector was obtained. Next, the obtained laminate was placed in a container having an active material-containing layer with a density of 2.2 g / cm. 3 The positive electrode roll was subjected to a roll press so that the positive electrode roll was obtained. The positive electrode roll obtained was punched out into a shape of 58 mm × 148 mm to prepare 90 positive electrodes.

[0150] A laminated electrode group was produced using the positive and negative electrodes and the polyethylene separator produced as described above. The positive and negative electrodes were set in an electrode laminate production device. The positive and negative electrodes were transported by a vacuum chuck of the laminate production device, and the polyethylene separator was sandwiched between the positive and negative electrodes in a zigzag shape to obtain a flat laminated electrode group. Thus, 10 sets of electrode laminates with 9 positive electrodes and 10 negative electrodes were produced. A positive electrode terminal and a negative electrode terminal were connected to this electrode group. In order to confirm the insulation of this laminated electrode group, an insulation resistance test was performed using an insulation resistance tester. When a direct current of 600 V was applied and the resistance was 5 MΩ or more, the electrode group was deemed to have passed. All 10 sets passed. Therefore, no internal short circuit was observed in the produced electrode group. <Example 5> 100 electrodes were prepared by the method of Example 2. These electrodes were used as negative electrodes. These negative electrodes were inserted into a container 51 of a case 50 shown in Figs. 20 and 21, sandwiched between a cover plate 52 and a bottom plate 53, and vacuum dried at 140°C for 12 hours. After drying, the moisture content of the negative electrodes located at the top and bottom outermost layers of the electrode stack and three negative electrodes located at the center was measured by Karl Fischer using the method described above, and the average value was calculated to be 345 ppm by mass.

[0151] Next, 90 positive electrodes were produced in the same manner as described in Example 4.

[0152] A laminated electrode group was produced using the positive and negative electrodes and the polyethylene separator produced as described above. The positive and negative electrodes were set in an electrode laminate production device. The positive and negative electrodes were transported by a vacuum chuck of the laminate production device, and the polyethylene separator was sandwiched between the positive and negative electrodes in a zigzag shape to obtain a flat laminated electrode group. Thus, 10 sets of electrode laminates with 9 positive electrodes and 10 negative electrodes were produced. A positive electrode terminal and a negative electrode terminal were connected to this electrode group. In order to confirm the insulation of this laminated electrode group, an insulation resistance test was performed using an insulation resistance tester. When a direct current of 600 V was applied and the resistance was 5 MΩ or more, the electrode group was deemed to have passed. All 10 sets passed. Therefore, no internal short circuit was observed in the produced electrode group.

[0153] According to the method for producing an electrode of at least one of these embodiments or examples, the method includes a step of obtaining a structure by applying a slurry containing at least one of a niobium-containing oxide and a titanium-containing oxide and water to a current collector, and a step of drying the slurry to form an active material-containing layer having a water content of 1,000 ppm by mass or more and 10,000 ppm by mass or less, as measured by the Karl Fischer method. Therefore, it is possible to suppress the occurrence of defects such as cracks, chips, and peeling in subsequent steps (e.g., pressing), and it is possible to provide a high-density electrode.

[0154] Although several embodiments of the present invention have been described, these embodiments are presented as examples and are not intended to limit the scope of the invention. These novel embodiments can be implemented in various other forms, and various omissions, substitutions, and modifications can be made without departing from the spirit of the invention. These embodiments and their modifications are included in the scope and spirit of the invention, and are included in the scope of the invention and its equivalents described in the claims.

[0155] The invention according to the embodiment will be described below. <1> A step of obtaining a structure by applying a slurry containing water and at least one of a niobium-containing oxide and a titanium-containing oxide to a current collector; a step of drying the slurry to form an active material-containing layer having a moisture content of 1000 ppm by mass or more and 10000 ppm by mass or less, as measured by the Karl Fischer method; pressing the structure; A method for producing an electrode comprising the steps of: <2> the coating is performed while the current collector is being moved in a transport direction, except for at least an end portion of the current collector parallel to the transport direction; The drying is performed while moving the structure in the transport direction and pulling the end portion of the structure in a direction intersecting the transport direction. <1> A method for producing the electrode according to claim 1. <3> The method further includes a step of adjusting a tension applied to the structure in a transport direction according to the moisture content. <1> or <2> A method for producing the electrode according to claim 1. <4> a step of stacking a plurality of the pressed structures and drying both outermost layers of the obtained stack while applying pressure to the stack, thereby reducing the moisture content of the active material-containing layer to 600 ppm by mass or less as measured by the Karl Fischer method; <1> ~ <3> 13. A method for producing the electrode according to any one of claims 1 to 12. <5> cutting the structure after pressing; a step of stacking a plurality of the cut structures and drying both outermost layers of the resulting stack while applying pressure to the stack, thereby reducing the moisture content of the active material-containing layer to 600 ppm by mass or less as measured by the Karl Fischer method; <1> ~ <4> 13. A method for producing the electrode according to any one of claims 1 to 12. <6> The niobium-containing oxide has the general formula Li x Ti 1-y M1 y Nb 2-z M2 z O 7+δ Niobium-containing oxides represented by the general formula Li x Ti 1-yM3 y+z Nb 2-z O 7-δ The niobium-containing oxide includes at least one selected from the group consisting of niobium-containing oxides represented by the formula: The M1 is at least one selected from the group consisting of Zr, Si, and Sn, the M2 is at least one selected from the group consisting of V, Ta, and Bi, the M3 is at least one selected from the group consisting of Mg, Fe, Ni, Co, W, Ta, and Mo, the x satisfies 0≦x≦5, the y satisfies 0≦y<1, the z satisfies 0≦z<2, and the δ satisfies -0.3≦δ≦0.3, <1> ~ <5> 13. A method for producing the electrode according to any one of claims 1 to 12. <7> The titanium-containing oxide includes at least one selected from the group consisting of monoclinic titanium dioxide, anatase titanium dioxide, rutile titanium dioxide, and bronze titanium dioxide. <1> ~ <6> 13. A method for producing the electrode according to any one of claims 1 to 12. <8> <1> ~ <7> a step of preparing an electrode group by using the electrode obtained by the method according to any one of the steps 1 to 5 as a first electrode and disposing a separator between the first electrode and a second electrode; A step of housing the electrode group in an exterior member; and causing the electrode group housed in the exterior member to retain a non-aqueous electrolyte. [Explanation of symbols]

[0156] Reference Signs List 1...electrode group, 2...exterior member, 3...negative electrode, 3a...negative electrode current collector, 3b...negative electrode active material-containing layer, 3c...negative electrode current collector tab, 4...separator, 5...positive electrode, 5a...positive electrode current collector, 5b...positive electrode active material-containing layer, 5c...positive electrode current collector tab, 6...negative electrode terminal, 7...positive electrode terminal, 10...structure, 20...slurry coating device, 21...drying furnace, 22...curve correction section, 23...slurry storage section, 24...first die coater, 25...second die coater, 26...current collector roll, 27...winding roller, F1...conveyor Feed path, 28...guide roller, 29...conveyor roller, 31...structural roll, 32...manufacturing apparatus, 33, 34...press rollers, 35-39...guide rollers, 40...winding section, 50...casing, 51...container, 52...cover plate, 53...bottom plate, 54...spring member, 100...secondary battery, S1...slurry coating, S2...first drying, S3...pressing, S4...cutting, S5...electrode group production, S6...storing electrode group in exterior member, S7...storing electrolyte in exterior member, S8...sealing, S9...second drying.

Claims

1. A step of obtaining a structure by applying a slurry containing water and at least one of a niobium-containing oxide and a titanium-containing oxide to a current collector; a step of drying the slurry to form an active material-containing layer having a moisture content of 1,000 ppm by mass or more and 10,000 ppm by mass or less as measured by Karl Fischer method; pressing the structure; A method for producing an electrode comprising the steps of:

2. the coating is performed while the current collector is being moved in a transport direction, except for at least an end portion of the current collector parallel to the transport direction; The method for manufacturing an electrode according to claim 1 , wherein the drying is performed while the structure is moved in the transport direction and while the end portion of the structure is pulled in a direction intersecting the transport direction.

3. The method for manufacturing an electrode according to claim 2 , further comprising the step of adjusting a tension applied to the structure in a transport direction according to the moisture content.

4. 2. The method for producing an electrode according to claim 1, further comprising the step of stacking a plurality of the pressed structures and drying both outermost layers of the obtained stack while applying pressure to the stack, thereby reducing the moisture content of the active material-containing layer to 600 ppm by mass or less as measured by the Karl Fischer method.

5. cutting the structure after pressing; 2. The method for producing an electrode according to claim 1, further comprising a step of stacking a plurality of the cut structures and drying both outermost layers of the obtained stack while applying pressure to the stack, thereby reducing the moisture content of the active material-containing layer to 600 ppm by mass or less as measured by the Karl Fischer method.

6. The niobium-containing oxide has the general formula Li x Ti 1-y M1 y Nb 2-z M2 z O 7+δ Niobium-containing oxides represented by the general formula Li x Ti 1-y M3 y+z Nb 2-z O 7-δ The niobium-containing oxide includes at least one selected from the group consisting of niobium-containing oxides represented by the formula:

2. The method for producing an electrode according to claim 1, wherein M1 is at least one selected from the group consisting of Zr, Si, and Sn, M2 is at least one selected from the group consisting of V, Ta, and Bi, M3 is at least one selected from the group consisting of Mg, Fe, Ni, Co, W, Ta, and Mo, x satisfies 0≦x≦5, y satisfies 0≦y<1, z satisfies 0≦z<2, and δ satisfies −0.3≦δ≦0.

3.

7. 2. The method for producing an electrode according to claim 1, wherein the titanium-containing oxide comprises at least one selected from the group consisting of monoclinic titanium dioxide, anatase titanium dioxide, rutile titanium dioxide, and bronze titanium dioxide.

8. a step of preparing an electrode group by using the electrode obtained by the method according to any one of claims 1 to 7 as a first electrode and disposing a separator between the first electrode and a second electrode; A step of housing the electrode group in an exterior member; and causing the electrode group housed in the exterior member to retain a non-aqueous electrolyte.

Citation Information

Patent Citations

  • Electrode for battery and its manufacture

    JP1997115504A

  • Positive electrode sheet and non-aqueous electrolyte secondary battery using the same

    JP1999025956A

  • Manufacturing method of electrode plate for nonaqueous electrolyte battery

    JP2005267997A

  • Method for manufacturing electrode for electrochemical element

    JP2008251776A

  • Electrode plate for nonaqueous electrolyte secondary battery, nonaqueous electrolyte secondary battery, and battery pack

    JP2012059569A